Alliance Reliability and Dispute Escalation. (April 2023) - Johnson, Jesse C; Wolford, Scott
States form defensive alliances hoping to deter adversaries and avoid war. However, scholars and policy analysts often worry that if an alliance fails to deter the promise of military support will encourage escalation, pushing disputants closer to war. We show that in many cases this concern is unwarranted. We use a game-theoretic model of alliance reliability and crisis bargaining to show that the same factors that indicate unreliability and provoke disputes also encourage alliance members to make concessions rather than risk war. We test this hypothesis using a sample of militarized disputes initiated against members of defensive alliances, where recent shifts in military capabilities represent changes in challengers' estimates of alliance reliability. Less-reliable alliances are less likely than reliable allies to deter disputes, but they also decrease the probability of escalation relative to reliable alliances. Unreliable alliances need not encourage war; rather, they can discourage it.